Large eddy simulation of auto-igniting methanol/n-dodecane blend spray flames - Shrestha, Bishal; Balogun, Fatimoh; Wan, Kevin; Yi, Junghwa; Wang-Alho, Huaying; Karimkashi, Shervin; Sirvio, Katriina; Manin, Julien; Mikulski, Maciej; Hyvönen, Jari; Kaario, Ossi (Elsevier, 2026)
The study investigates the auto-ignition characteristics of methanol/n-dodecane fuel blends at varying blend ratios and ambient temperatures using large eddy simulation (LES) in OpenFOAM with the Engine Combustion Network (ECN) Spray-D injector. The primary objective is to determine the maximum methanol fraction in the blend that enables stable combustion with an engine-relevant ignition delay time (IDT) below 1 ms at ambient temperatures of 900, 950, 1000, and 1100 K. The numerical framework validation is performed against existing ECN n-dodecane data, new ECN experiments for pure methanol, and new methanol–octanol–diesel blend experiments from the Combustion Research Unit (CRU). Four cases satisfy the IDT criterion: (I) 10% methanol, 90% n-dodecane at 900 K, (II) 20%–80% at 950 K, (III) 30%–70% at 1000 K, and (IV) 70%–30% at 1100 K. Increasing the methanol content suppresses ignition due to methanol’s high heat of vaporisation and net consumption of OH radical at low temperatures. Ignition occurs under rich conditions for cases I and II, near stoichiometric conditions for case III, and under lean conditions for the methanol-dominant case IV. Case IV exhibits elevated centre-line temperature, increased NO emissions, and reduced C2H2 formation. Despite these differences, all cases display a similar heat release rate at quasi steady-state.
Keywords: Methanol/n-dodecane blends; ECN spray D; Experimental validation; Combustion; Adaptive mesh refinement; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|